Notes on Early Land Plants Today. 21. On Archilejeunea herminieri (Lejeuneaceae, Marchantiophyta) - Gradstein, S. Robbert (Phytotaxa, 2013)
In a revision of Archilejeunea (Spruce 1884: 88) Stephani (1888: 113) in tropical America, Gradstein & Buskes (1985) suggested that Archilejeunea herminieri might be conspecific with Amblyolejeunea fulfordiae Jovet-Ast (1949: 25) (≡ Lejeunea fulfordiae (Ast) Zhu & Cheng (2008: 617)). The identity of the material could not be ascertained with certainty because perianths, which are characteristically inflated and without keels in Lejeunea fulfordiae, were lacking and the hyaline papilla at the lobule apex was not observed. Now, 25 years later, my re-examination of the type specimen has revealed that the material is identical to Oryzolejeunea saccatiloba (= Oryzolejeunea antillana). When sterile, Oryzolejeunea saccatiloba is confusingly similar to Lejeunea fulfordiae. Both species have undivided, rounded underleaves, stems with ventral merophytes 2 cells wide, somewhat falcate leaf-lobes with rounded apex, crenulate leaf margins with large, thin-walled cells, and large leaf-lobules with a truncate apex and a short, obtuse apical tooth. However, Oryzolejeunea saccatiloba has a distal hyaline papilla (which now has been observed in the type material of Archilejeunea herminieri, admittedly with some difficulty), the distal free margin of the lobules bordered by cells that are similar in size to the inner lobule cells, and lobe cells with an asperulate cuticle (but occasionally smooth; see Bernecker-Lücking 1999). In Lejeunea fulfordiae, however, the hyaline papilla is proximal, the distal free margin is bordered by enlarged cells (Zhu & Cheng 2008, Fig. 1: I), and the cuticle of the lobe cells is always smooth. The lack of a border of enlarged cells on the distal free margin, the distinctly asperulate lobe cells and the distal hyaline papilla in Archilejeunea herminieri leave no doubt about the identity of the species.